Wealth inequality in Latin America (2000–2020): data, facts and conjectures - Carranza, R; De Rosa, M; Flores, I (Oxford University Press, 2025)
How has wealth accumulated in Latin America and how is it distributed across households? Despite the region being widely recognized for its extreme income inequality, data on wealth are scarce, partial and often contradictory, making it difficult to answer these basic questions. We estimate wealth aggregates based on macroeconomic data and wealth inequality based on recently available surveys and on administrative data. We contrast our results with those in the literature, with a handful of estimates from administrative sources, and with estimates from Credit Suisse and wid.world. In considering all the evidence, we distinguish reliable facts from what can only be conjectured or speculated. We find that aggregate wealth increased over two decades in four countries, and that wealth inequality is extremely high where it can be measured (with a top 1% share of up to 40%), which is likely to be the case for the whole region.